2014
DOI: 10.4202/app.00074.2014
|View full text |Cite
|
Sign up to set email alerts
|

Osteohistology of hyperodapedontine rhynchosaurs (Diapsida, Archosauromorpha) from the Upper Triassic of Southern Brazil.

Abstract: The first osteohistological study focused exclusively on rhynchosaurs (non-archosauriform archosauromorphs), based on the hyperodapedontines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In the Kupferzell locality, fluctuating growth marks in the temnospondyl Gerrothorax pulcherrimus have been interpreted as evidence for unstable environmental parameters (Witzmann et al, 2012) so that the fast growth rates present in Batrachotomus may have been an advantage to an apex predator niche in the ecosystem (Both-Brink et al, 2016). Thus, besides phylogenetic constraints, the bone tissue of Batrachotomus probably includes an adaptational signal, as was suggested several times before (Ricql es et al, 2003(Ricql es et al, , 2008BothaBrink and Smith, 2011;Veiga et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the Kupferzell locality, fluctuating growth marks in the temnospondyl Gerrothorax pulcherrimus have been interpreted as evidence for unstable environmental parameters (Witzmann et al, 2012) so that the fast growth rates present in Batrachotomus may have been an advantage to an apex predator niche in the ecosystem (Both-Brink et al, 2016). Thus, besides phylogenetic constraints, the bone tissue of Batrachotomus probably includes an adaptational signal, as was suggested several times before (Ricql es et al, 2003(Ricql es et al, , 2008BothaBrink and Smith, 2011;Veiga et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
“…Data on archosauromorphs, archosauriforms, and pseudosuchian archosaurs, however, are still rare (and less well understood) but so far show a variety of bone tissues and vascular systems, resulting in a mixture of bone tissue patterns (Botha-Brink and Smith, 2011). The primary bone tissue type of non-ornithodiran archosauromorphs can be characterized (with a few exceptions, see below) as lamellar-zonal bone tissue type/LZB (Ricql es et al, 2003(Ricql es et al, , 2008Botha-Brink and Smith, 2011;Werning and Irmis, 2011;Ezcurra et al, 2014;Mukherjee, 2015;Veiga et al, 2015;Werning and Nesbitt, 2016). Differences with modern reptiles that also grow with LZB are mainly related to vascularity (density and organization) and a higher organization of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The bone histology of non-archosaurian archosauromorphs has received great attention in the last decade (Ricqlès et al 2008; Nesbitt et al 2009; Botha-Brink and Smith 2011; Werning and Irmis 2011; Legendre et al 2013, 2016; Ezcurra et al 2014; Mukherjee 2015; Veiga et al 2015; Werning and Nesbitt 2016; Jaquier and Scheyer 2017). Ricqlès et al (2008) suggested that the capacity of reaching and maintaining very high bone growth rates is an apomorphic feature of archosauriforms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Veiga et al . (in press) examined the available long bone microstructure of the Late Triassic hyperodapedontines, Teyumbaita sulcognathus and Hyperodapedon sp., and showed that hyperodapedontines had faster initial growth in comparison with the latter.…”
mentioning
confidence: 99%